(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This research focus on investigating the differences between locative prepositional phrases coming with variety of noun including different contents. They are concerning with links with locative prepositions and nouns connecting with in the sentences, while expressing placement, location or direction with locative compounds. Taken many fiction books of English literature are identified types of nouns denoting the feature of locativivity by exploiting samples in the work. This study presents distinctive and similar peculiarities of locative category with nouns. The analyse shows the characteristics of locative syntaxemes in the statements.